1985
DOI: 10.1038/313689a0
|View full text |Cite
|
Sign up to set email alerts
|

Derivation of mouse intestinal crypts from single progenitor cells

Abstract: Adult intestinal epithelium consists of a sheet of single-cell thickness which is morphologically highly organized into tubular invaginations (crypts) and finger-like projections (villi). Proliferation of the cells is confined to the base of the crypts, from which cells migrate to the villi, where they are shed. The villi are formed during embryogenesis from a multilayered epithelium. In mice, crypts develop at about the time of birth from the epithelium between the villi, which by this stage is no longer mult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
158
0

Year Published

1991
1991
2002
2002

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 309 publications
(164 citation statements)
references
References 9 publications
6
158
0
Order By: Relevance
“…The simplest explanation for the fact that the mutations found in normal mucosa were clonal is that p53 mutation confers a growth advantage, although it is also consistent with mutagenesis of stem cells in the basal cell layer. Stem cells have not been clearly identi®ed in the upper aero-digestive tract, but studies on intestinal epithelium of chimaeric mice revealed that whole crypts derive from single stem cells (Ponder et al, 1985), and our results would be compatible with large contributions of individual stem cells to upper aerodigestive epithelium. When the mutant RNA content of a biopsy exceeds 50% it is likely that the mutant clone has lost the wild type allele, since both alleles are normally equally expressed (Ishioka et al, 1993).…”
Section: Discussionsupporting
confidence: 76%
“…The simplest explanation for the fact that the mutations found in normal mucosa were clonal is that p53 mutation confers a growth advantage, although it is also consistent with mutagenesis of stem cells in the basal cell layer. Stem cells have not been clearly identi®ed in the upper aero-digestive tract, but studies on intestinal epithelium of chimaeric mice revealed that whole crypts derive from single stem cells (Ponder et al, 1985), and our results would be compatible with large contributions of individual stem cells to upper aerodigestive epithelium. When the mutant RNA content of a biopsy exceeds 50% it is likely that the mutant clone has lost the wild type allele, since both alleles are normally equally expressed (Ishioka et al, 1993).…”
Section: Discussionsupporting
confidence: 76%
“…We envisage a model of random stochastic loss of clones during adult life and predict that the number of coherent limbal clones drops further as the mice age. This process may be analogous to the stochastic process of crypt purification in the small intestine of mosaics and chimeras (Ponder et al, 1985;Schmidt et al, 1988).…”
Section: Discussionmentioning
confidence: 99%
“…Enteroendocrine cells, enterocytes, goblet cells, and Paneth cells all arise from common pluripotent stem cells located in the base of the crypts of Leiberkuhn (Cheng and Leblond, 1974a;Ponder et al, 1985;Roth et al, 1992). Descendants of these stem cells differentiate into endocrine cells, enterocytes, and goblet cells, which predominantly migrate out of the crypt onto the villus, or into Paneth cells, which migrate to the base of the crypt (Cheng and Leblond, 1974a).…”
Section: Introductionmentioning
confidence: 99%